2013
DOI: 10.1002/erv.2235
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Guided Self‐help Incorporating a Mobile Component in People with Eating Disorders: A Pilot Study

Abstract: A guided self-help intervention incorporating a mobile component was both acceptable and associated with symptom change in people with EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Nineteen studies (83%) examined programs which the authors reported to be CBT‐based. Five studies did not use CBT as their primary intervention and described using a mix of psychoeducation, self‐monitoring and motivational interviewing (Aardoom et al, ; Cardi et al, ; Hötzel et al, ; Leung et al, ; Strandskov et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies (83%) examined programs which the authors reported to be CBT‐based. Five studies did not use CBT as their primary intervention and described using a mix of psychoeducation, self‐monitoring and motivational interviewing (Aardoom et al, ; Cardi et al, ; Hötzel et al, ; Leung et al, ; Strandskov et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of sessions varied from one session (Barakat et al, ) to 16 sessions (Jones et al, ). The length of the interventions also varied greatly across the studies from 3 weeks (Cardi et al, ) to 28 weeks (Wagner et al, ), with a mean duration of 13.78 weeks ( SD = 6.88).…”
Section: Resultsmentioning
confidence: 99%
“…Mobile apps can enhance psychoeducation by delivering clear and concise psychoeducational information linked to the topics being covered in therapy. As psychoeducation is seen as a major component of mobile intervention [50], it has been incorporated into several mobile apps, some of which have been shown to be efficacious in treating various psychiatric conditions, including stress [51], anxiety and depression [52], eating disorders [53], PTSD [54], and obsessive compulsive disorder (OCD) [55]. For example, Mayo Clinic Anxiety Coach is a mobile phone app “designed to deliver CBT for anxiety disorders, including OCD” [55].…”
Section: A Proposed List Of Essential Features For Mobile Apps That Omentioning
confidence: 99%
“…It also focuses exclusively on palatable food intake and not on the consumption of all foods in general (Steptoe, Pollard, & Wardle, 1995). Individuals are not always aware of the motives behind their behavior and being aware of their motives is often the first step in changing behavior (Bandura, 1977; Cardi, Clarke, & Treasure, 2013). The PEMS is a tool that brings awareness to both the person being tested and the tester regarding the person’s motives behind consuming highly palatable foods or drinks.…”
Section: Introductionmentioning
confidence: 99%